Endoscopic gastric reduction with an endoluminal suturing device: a multicenter prospective trial with 1-year follow-up - Huberty, Vincent; Machytka, Evzen; Boškoski, Ivo; Barea, Marie; Costamagna, Guido; Deviere, Jacques (Endoscopy, 2018)
Background Obesity is the pandemic disease of this century. Surgery is the only effective treatment but cannot be offered to every patient. Endoscopic sutured gastroplasty is a minimally invasive technique that may potentially fill the gap between surgery and behavioral therapy. In this study, we prospectively investigated the efficacy and safety of a novel suturing device.Methods After a pre-bariatric multidisciplinary work-up, class 1 and 2 obese patients were included. Using a simple triangulation platform, transmural sutures with serosa-to-serosa apposition were performed in the gastric cavity. Patients were followed according to the same routines as those performed for bariatric procedures.Results Between November 2015 and December 2016, 51 patients were included across three European Centers. Mean body mass index at baseline was 35.1 kg/m2 (SD 3.0). Excess weight loss and total body weight loss at 1 year were 29 % (SD 28) and 7.4 % (SD 7), respectively, for the whole cohort (45 patients). At follow-up gastroscopy, 88 % of sutures were still in place (30 patients). No severe adverse events were observed.Conclusions Endoscopic sutured gastroplasty using this novel device is safe and achieved weight loss results in line with criteria expected for these endoluminal techniques. Further prospective studies vs. placebo or nutritional support are needed.